Formulation and Investigation of an Integral Equation for Characteristic Functions of Positive Random Variables - Artikis, Constantinos T. (Communications in Mathematics and Applications, 2021)
Functional equations of characteristic functions constitute power research tools for establishing new results in several significant areas of probability theory. The present paper makes use of the characteristic functions of two Poisson random sums and the concept of equality in distribution for introducing an important selfdecomposable distribution.
Keywords: Characteristic function; Random sum; Functional equation